2006
DOI: 10.3201/eid1202.050404
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydophila psittaciin Fulmars, the Faroe Islands

Abstract: Chlamydophila psittaci was detected in 10% of 431 fulmars examined from the Faroe Islands. Analysis of ompA showed a sequence almost identical to that of the type strain. The origin of C. psittaci outbreaks in fulmars is discussed. Despite a high level of exposure, the risk for transmission of C. psittaci to humans is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 13 publications
3
33
0
1
Order By: Relevance
“…Previous studies also based on molecular detection and in species with significant sample numbers (about 30 birds) reported a prevalence of 11% on average (ranging from Ͻ1 to 38% depending on the species) (21,22,26,32). Regarding Laridae, Christerson et al (26) reported an average prevalence of 17%.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies also based on molecular detection and in species with significant sample numbers (about 30 birds) reported a prevalence of 11% on average (ranging from Ͻ1 to 38% depending on the species) (21,22,26,32). Regarding Laridae, Christerson et al (26) reported an average prevalence of 17%.…”
Section: Discussionmentioning
confidence: 97%
“…Cloacal shedding of Chlamydiaceae was detected here in four bird families, including the Sulidae family, never studied before. To date, Chlamydiaceae species had been detected in the Stercoraccidae, Procellaridae, Scolopacidae, Alcidae, Anatidae, Sternidae, and Laridae families (21,22,25,26,32). At the bird species level, the present study revealed the occurrence of Chlamydiaceae in six seabird species, with three of them being more represented in significant numbers (European herring gulls, northern gannets, and common murres, in rank order) and more frequently admitted into WRCs from the French coasts of the Bay of Biscay and the Channel (Union Française des Centres de Sauvegarde, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the different species show a high degree of host specificity, other hosts may also be susceptible to infection as these organisms have been isolated from a variety of mammals (4,6,17), birds (10,11), and reptiles (3,6). Chlamydia trachomatis (C. trachomatis) and Chlamydophila pneumoniae (Cp.…”
mentioning
confidence: 99%
“…Further, both C. psittaci and non-classified members of Chlamydiae have been found in seabird and penguin species (Herrmann et al 2000(Herrmann et al , 2006Kaleta and Taday 2003;Barbosa and Palacios 2009;Christerson et al 2010); however, the true range and breadth of presence and prevalence are unknown. As is the case for C. psittaci, seabirds may act as transmission vehicles, migrating over large distances and often sharing their habitats with humans.…”
Section: Introductionmentioning
confidence: 99%